Peripheral Nervous System-Machine Interfaces, 2nd Edition - Claudio Castellini (Frontiers Research Topics, 2018)
For 5 years, the Peripheral Nervous System-Machine Interfaces workgroup has dedicated itself to the recruitment of researchers, clinicians, and general public in a unified effort to advance the frontier of restoration of quality of life to those with limb deficiency. Our group's mission is to bring together experts from various domains to identify promising new technologies and new opportunities for inquiry and discovery in prosthetics research. This e-Book collects 10 cutting edge research articles written by members of the workgroup, covering three domains prioritized by the workgroup: novel prosthetic technology, approaches for reducing device rejection, and prosthetic control. In our summary editorial, we four principals of the workgroup reflect on our first 5 years, and project our vision for the future, as the Society for Prosthetics.